Small bowel obstruction secondary to foam earplug ingestion - Duncan McGrouther; Robert McCusker; Daniel Carroll (Elsevier, 2020)
We describe a case of a 12 month old male who presented with small bowel obstruction (SBO) secondary to ingestion of a foam ear plug. Both X-ray and ultrasound failed to pick up the cause of obstruction. Laparotomy and removal of the object led to an uncomplicated recovery. This case highlights the need to consider foam and other expanding substances as potential causes of small bowel obstruction in infants. Keywords: Foam earplug, Ingested foreign bodies, Small bowel obstruction